Design of Multifunctional Vest Bag for Moving Coffee Traders - Chalifh Azfari; Geggy Gamal Surya (Fakultas Seni Rupa dan Desain, Institut Seni Indonesia Surakarta, 2025)
Traveling coffee traders are one of the jobs in the informal sector that are very often found in the Jabodetabek area. Traveling coffee traders are also considered as one of the efforts to overcome unemployment by creating their own jobs through entrepreneurship that is cheap to do and often found in any area. Usually, traveling coffee traders use public spaces to sell, such as sidewalks and parks. However, although their existence is often considered to disturb the beauty of the city, many people consider that the existence of traveling coffee traders plays an important role when needed, such as during office breaks, when taking a break while traveling and so on. The use of a multifunctional product will greatly help the smoothness of sales operations carried out by traveling coffee traders. With this new breakthrough, products and services are easier to reach potential consumers widely. Therefore, the idea arose for this research to design a multifunctional vest design for traveling traders who can carry their needs when selling a product and add their own appeal.